2010
DOI: 10.1103/physrevd.81.115002
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive excited leptons search in two lepton final states at the CERN LHC

Abstract: We study the potential of the exclusive pp → pℓ − ℓ + p process to probe excited leptons at the LHC which is known to be one of the most clean channel at the hadron colliders. The sensitivity of the model parameters is obtained 95% confidence level by considering three forward detector acceptances; 0.0015 < ξ < 0.5, 0.0015 < ξ < 0.15 and 0.1 < ξ < 0.5. * sceminan@cumhuriyet.edu.tr

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Experimental results on exclusive twophoton production of W + W − and + − pairs in γ γ interactions reported by the CMS and ATLAS Collaborations [9][10][11][12] have demonstrated that it is possible to measure such events with the experimental apparatus already available at the LHC, allowing for novel studies of QCD at very high energies and searches for Beyond Standard Model Physics (see, e.g., Ref. [49][50][51][52][53][54][55][56][57][58][59]). This motivates us to revisit the analysis of double vector meson production in ultra peripheral heavy ion collisions performed some time ago in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results on exclusive twophoton production of W + W − and + − pairs in γ γ interactions reported by the CMS and ATLAS Collaborations [9][10][11][12] have demonstrated that it is possible to measure such events with the experimental apparatus already available at the LHC, allowing for novel studies of QCD at very high energies and searches for Beyond Standard Model Physics (see, e.g., Ref. [49][50][51][52][53][54][55][56][57][58][59]). This motivates us to revisit the analysis of double vector meson production in ultra peripheral heavy ion collisions performed some time ago in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, an exclusive excited leptons search in the pp ! pl À l þ p reaction at the LHC was studied in [11].…”
Section: Introductionmentioning
confidence: 99%
“…New physics searches in photon-induced interactions at the LHC have been discussed in the literature [17][18][19][25][26][27][28][29][30][31][32][33]. A detailed analysis of WW couplings has been done in [26] via the process pp !…”
Section: Introductionmentioning
confidence: 99%